The effect of channel deepening on tides and storm surge: A case study of Wilmington, NC - R. Familkhalili; S. A. Talke (Geophysical Research Letters)
Abstract In this study we investigate the hypothesis that increasing channel depth in estuaries can amplify both tides and storm surge by developing an idealized numerical model representing the 1888, 1975, and 2015 bathymetric conditions of the Cape Fear River Estuary, NC. Archival tide gauge data recovered from the U.S. National Archives indicates that mean tidal range in Wilmington has doubled to 1.55 m since the 1880s, with a much smaller increase of 0.07 m observed near the ocean boundary. These tidal changes are reproduced by simulating channel depths of 7 m (1888 condition) and 15.5 m (modern condition). Similarly, model sensitivity studies using idealized, parametric tropical cyclones suggest that the storm surge in the worst‐case, CAT‐5 event may have increased from 3.8 ± 0.25 m to 5.6 ± 0.6 m since the nineteenth century. The amplification in both tides and storm surge is influenced by reduced hydraulic drag caused by greater mean depths.